Back Cover: Applications of carbon dots on tumour theranostics (View 2/2021). Issue 2 (8th April 2021) - Wu, Hao; Su, Wen; Xu, Huimin; Zhang, Yang; Li, Yunchao; Li, Xiaohong; Fan, Louzhen
Abstract : Carbon dots are a type of zero‐dimensional carbon‐based nanomaterials (resembling a Chinese knot), exhibiting low cytotoxicity, high water solubility, favorable biocompatibility and good photostability. In article number 20200061, Yang Zhang, Louzhen Fan, Hao Wu and co‐workers have updated the latest development of carbon dots from their use as bioimaging agents to multifunctional tumor theranostic systems as well as their development of preparation, hydrophilicity, biotoxicity and optical properties.